Organic fertilizer increases pumpkin production by improving soil fertility - Ren, Fangfang; Zhang, Jinxia; Ding, Lin; Zhang, Rui; Li, Fuqiang; Li, Xuan; Zhong, Tao; Yin, Meng; Yang, Runheng; Tian, Pengliang; Du, Liangliang; Gan, Kaiyuan; et al. (Frontiers in Plant Science, 2024)
Compared with long-term and continuous application of large amounts of chemical fertilizers, fertilizers with microbial organic nutrient sources can improve soil environment, increase soil fertility and increase crop yield. In view of the current low soil fertility and poor soil environment leading to low crop yield and instability in the arid regions of northwest China, the effects of organic fertilizer with microbial nutrient sources on soil nutrients and pumpkin yield were studied in 2022 and 2023 in this region. The fertilizer application level was used as control factor, with four treatments of low level (L), medium level (M), high level (H), and a conventional fertilizer control (CK). The results showed that the high application level of organic fertilizer was more beneficial to the growth of pumpkin, and the stem diameter, vine length, and leaf area of pumpkin under H treatment were the highest from 2022 to 2023. Compared to CK, the average soil bulk density was significantly decreased by 8.2718.51% (P< 0.05); the soil organic carbon, available phosphorus, available potassium, and nitrate nitrogen under H treatment were increased by an average of 32.37%, 21.85%, 18.70%, and 36.97%, respectively. Under different organic fertilizer treatments, the pumpkin yield under M treatment was the highest, reaching 30926.18 kg•ha -1 , followed by H treatment. compared to CK, M and H treatments increased the yield by 25.26% and 7.01%, respectively, and improved water use efficiency by 14.18% and 2.21%, respectively. Redundancy analysis (RDA) of soil nutrients, pumpkin growth dynamics and yield in 2022 and 2023 showed that soil organic carbon, available phosphorus, available potassium, nitrate nitrogen, and water use efficiency were significantly positively correlated with pumpkin yield (P<0.01). In conclusion, H and M treatments can improve soil fertility promote pumpkin growth and development, and ultimately increase pumpkin yield. In summary, medium organic fertilizer